2019
DOI: 10.4049/jimmunol.1801594
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Mediated Compensatory Immunity to Mycobacterium avium in the Absence of Macrophage Activation by IFN-γ

Abstract: Granuloma formation is a hallmark of several infectious diseases, including those caused by Mycobacterium sp. These structures are composed of accumulations of inflammatory cells, and it has been shown that cytokines such as IFN-g and TNF-a are required for granuloma assembly during M. avium infections in mice. Macrophages (MFs) insensitive to IFN-g (MIIG) mice have MFs, monocytes, and dendritic cells that are unresponsive to IFN-g. We observed that although IFN-g 2/2 mice present an exacerbated infection, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…did not show exacerbated lesions). This result is in line with previous studies that showed that immunodeficient mice or IFN-γ −/mice developed increased bacterial burdens without exacerbated lung pathology and that failure of granuloma formation via macrophages and lymphocytes made the mice susceptible to Mav infection [45][46][47]. Therefore, we postulate that our results at 10 w.p.i.…”
Section: Figure 3 Alteration Of the Cellular Composition In The Lungs By Mycobacterium Avium (Mav) Infection Accompanied By Allergic Asthsupporting
confidence: 93%
“…did not show exacerbated lesions). This result is in line with previous studies that showed that immunodeficient mice or IFN-γ −/mice developed increased bacterial burdens without exacerbated lung pathology and that failure of granuloma formation via macrophages and lymphocytes made the mice susceptible to Mav infection [45][46][47]. Therefore, we postulate that our results at 10 w.p.i.…”
Section: Figure 3 Alteration Of the Cellular Composition In The Lungs By Mycobacterium Avium (Mav) Infection Accompanied By Allergic Asthsupporting
confidence: 93%
“…93 This highlights an essential difference between Mtb bacterial control with IFNγ and M avium control with TNFα. 94 More recent studies have shown that mice can control M avium infections independently of macrophage activation by IFNγ, with TNFα compensating for the lack of IFNγ activation by IFNγ. 94 Moreover, the M avium granuloma development forms without the aid of IFNγ activation of macrophages.…”
Section: Disseminated Mac (Dmac) Is Almost Exclusively Seen In Patientsmentioning
confidence: 99%
“…94 More recent studies have shown that mice can control M avium infections independently of macrophage activation by IFNγ, with TNFα compensating for the lack of IFNγ activation by IFNγ. 94 Moreover, the M avium granuloma development forms without the aid of IFNγ activation of macrophages. 94 Early studies showed that M avium strains could show different morphotypes, which could impact the strain's virulence properties.…”
Section: Disseminated Mac (Dmac) Is Almost Exclusively Seen In Patientsmentioning
confidence: 99%
See 2 more Smart Citations